2008
DOI: 10.1007/s10350-008-9329-x
|View full text |Cite
|
Sign up to set email alerts
|

Minimal Surgery for Pilonidal Disease Using Trephines: Description of a New Technique and Long-Term Outcomes in 1,358 Patients

Abstract: Compared with frequently used pilonidal operations, the trephine technique is associated with a lower recurrence rate and a low postoperative morbidity rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
139
2
14

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(157 citation statements)
references
References 12 publications
2
139
2
14
Order By: Relevance
“…In a recent study of 1435 patients the midline pits and secondary openings were simply cored out using skin trephines and the abscesses were cleaned out through the trephines, which were left unsutured. There was a 16·2 per cent recurrence rate with a mean follow-up of 6·9 years 76 .…”
Section: Simple Surgical Procedures Without Wide Excision Of Abscessesmentioning
confidence: 97%
“…In a recent study of 1435 patients the midline pits and secondary openings were simply cored out using skin trephines and the abscesses were cleaned out through the trephines, which were left unsutured. There was a 16·2 per cent recurrence rate with a mean follow-up of 6·9 years 76 .…”
Section: Simple Surgical Procedures Without Wide Excision Of Abscessesmentioning
confidence: 97%
“…However, in the minimal surgical procedure recurrence, rates increased over the span of a year (7). Many publications have shown that recurrence occurred in the first 5 years (19)(20)(21). Soll et al demonstrated that recurrence rates for PS treated with the minimal surgical procedure increased annually, and they gave the recurrence rates as 6.5%, 13.2%, and 16.2% for the first year, the first 5 years, and the first 10 years, respectively (7).…”
Section: Discussionmentioning
confidence: 99%
“…Inwieweit zukünftig die "minimalinvasiven" Techniken des "pitpicking", also der alleinigen Entfernung von penetrierenden Haaren, Einzug halten werden, bleibt abzuwarten [2,3]. Gegen das "pitpicking" spricht, dass in regelmäßigen Abständen Publikationen über die Sicherung eines Plattenepithelkarzinoms oder anderer maligner Befunde aus einem Pilonidalsinus erscheinen [33,34].…”
Section: Diskussionunclassified
“…Die eine sieht die PSE als Krankheitsbild der Haare in gesunder Haut, und dementsprechend besteht der Therapieansatz in der Entfernung der Haare, wonach die PSE ausheilen soll [1,2]. Dieser Ansatz hat in letzter Zeit zu einer Reihe von "minimalinvasiven" Therapieempfehlungen geführt, deren Ergebnisse sehr vielversprechend sind, deren wissenschaftliche Untermauerung aber noch aussteht [2,3]. Die andere, eher konservative Betrachtung der PSE beschreibt den Pilonidalsinus als chronisch granulierende Krankheit der Haut und Unterhaut, und dementsprechend beruht der Therapieansatz auf der Entfernung des gesamten chronisch infizierten Komplexes.…”
unclassified